Electroencephalographic and peripheral temperature dynamics during a prolonged psychomotor vigilance task. (May 2019) - Molina, Enrique; Sanabria, Daniel; Jung, Tzyy-Ping; Correa, Ángel
Highlights: A 45-min PVT assessed fatigue and attentional fluctuations. EEG and skin temperature were recorded to predict performance. Frequency power of the EEG and skin temperature showed a direct relationship with RT. Frequency power of the EEG was a potential predictor of lapses of attention. These findings provided insight to prevent accidents and improve safety. Abstract: Attention lapses and fatigue are a main source of impaired performance that can lead to accidents. This study analyzed electroencephalographic (EEG) dynamics and body skin temperature as markers of attentional fluctuations in non-sleep deprived subjects during a 45 min Psychomotor Vigilance Task (PVT). Independent Component Analysis and time-frequency analysis were used to evaluate the EEG data. Results showed a positive association between distal and distal-to-proximal gradient (DPG) temperatures and reaction time (RT); increments in EEG power in alpha-, theta- and beta-band frequencies in parieto-occipital, central-medial and frontal components, were associated with poor performance (slower RT) in the task. This generalized power increment fits with an increased activity in the default mode network, associated with attention lapses. This study highlights the potential use of the PVT as a tool to obtain individual physiological indices of vigilance and fatigue that could be applied to other vigilance tasks typically performed in occupational settings.